Maternal Fetal Medicine Physician Understanding, Attitudes, and Practice in Regards to New Abortion Legislation [18J]. (May 2020) - Morgan, Elizabeth A.; Miller, Jill; Thompson, Rachel; Jones, Cresta W.
Abstract : INTRODUCTION: Second trimester diagnosis of congenital anomalies and genetic disorders is often performed by Maternal Fetal Medicine (MFM) Physicians, who counsel on available options including termination of pregnancy (TOP). Recent abortion legislation, including implementation of gestational age limits, waiting periods, and mandatory counseling, can directly influence these conversations with patients. The Guttmacher Institute reports 58 such restrictions in the first half of 2019 alone. The purpose of this study was to understand how MFM Physicians perceive these legislative changes and whether they modify clinical practice in response. METHODS: We mailed an anonymous survey to all physician members of the Society of Maternal Fetal Medicine in January 2018 and again in April 2019. The survey included questions on physician demographics, knowledge of abortion legislative changes in the past five years, and impact on clinical practice. RESULTS: Of 2217 surveys mailed, 686 (30.3%) physicians responded. 33.2% of respondents reported changes to abortion provision legislation, 53.4% denied changes and 13.4% were unsure. In 30 of the 47 states represented, MFMs disagreed whether there were changes to legislation in their state. Of the 359 physicians reporting new legislation, 243 (67.7%) stated they changed clinical practice in response. Physicians also reported concerns with increasingly necessary out of state referrals, as well as rushed decision making and increasing financial burdens to low-income patients. CONCLUSION: There was significant variation in MFM Physician response regarding changes to abortion legislation. Many MFMs reported changes to legislation resulting in alterations of clinical practice and voiced concerns in regards to increasing patient burdens.